The Effects of Optical Power of Semiconductor Laser on the Characteristics of Si-diode in an Exposed Device - Mohammad, Musab S.; Rasool, Raad A.; Jassim, Fathi M. (Iraqi Journal of Science, 2021)
In this paper, we experimentally studied the effects of optical power of semiconductor laser on the electrical properties of silicon diode of an exposed device. The experimental results showed that the laser diode light of different optical powers (2, 3, and 4 mW) had effects on the silicon diode that are somewhat similar to those of thermal treatment. A shift in the current-voltage curve to the left side was also noticed, which led to a non-linear decrease of the barrier voltage of the diode by the effect of laser light. We also reveal a decrease by 344.8 nA/mW in the reverse saturation current of the silicon diode as a result of exposure to laser light. The forward resistance of the silicon diode decreased with increased incident optical power. The value of the maximum current of diode increased by 0.5 A/W with increasing the optical power incident on the diode.